PENGARUH BAURAN PEMASARAN TERHADAP CITRA (IMAGE) MUSEUM ANGKUT SEBAGAI WISATA YANG BERWAWASAN INFORMASI, EDUKASI, DAN REKREASI (Survey Pada Mahasiswa UNISMA Fakultas Ekonomi dan Bisnis Jurusan Manajemen JL.MT.Haryono 193 Malang) - Dedi Prayogo; N Rachma (UNIVERSITAS ISLAM MALANG, 2018)
ABSTRACTThis research is meant to find the effect of experiential marketing of image museum angkut as information tours. education tours, and recreation tours. Independent variables use in this research is product, price, promotion, place, people, physical evidence, process and dependent variables is image. The sampling technique was conducted by purposive sampling method. The data used in this study is primary data. This type of research belong to explanatory research. The population of this current study was all university students in economy major at UNISMA who had fulfilled the registration fee. Data analysis method used in this research is using multiplelinier regression analysiswith t test hypothesis. The result of this study indicate that partially physical evidence, and process significant effect on image museum angkut as education tours, recreation tours and information tours. While product, price, promotion, place, and people partially no significant effect on image museum angkut as education tours, recreation tours and information tours .Keywords : Experiential marketing (product, price, promotion, place, people, physical evidence, process),(image).